Melon jellies in shell and enriched with mandacaru seeds - Reis, Carolaine Gomes dos; Figueiredo, Rossana Maria Feitosa de; Queiroz, Alexandre José de Melo; Amadeu, Lumara Tatiely Santos; Lima, Thalis Leandro Bezerra de; Costa, Patrícia da Silva (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The production of jams with the addition of residues from fruit processing, such as peels and seeds, can reduce environmental impacts and nutritionally enrich the products. With a view to using the residues from the melon and mandacaru processing, as well as minimizing the post-harvest losses of these fruits, the objective was to develop and characterize three formulations of cv. ‘Orange Flesh’, plus melon peel and mandacaru seeds. The jellies were characterized according to the physical-chemical parameters (pH, total titratable acidity, total sugars, reducing and non-reducing sugars, total soluble solids, water content, water and ash activity) and bioactive compounds (ascorbic acid, total phenolic compounds, total anthocyanins and total flavonoids). From the elaborated jellies it was observed that the formulation with the addition of the cooked melon peels (F3), was the one that obtained the highest levels of bioactive compounds, such as phenolic compounds 39.98 mg 100-1 g-1, however the formulations F2 (melon jelly with 1% mandacaru seeds) and F1 (melon jelly) obtained good results. The melon pulp, its peels and mandacaru seeds proved to be viable alternatives in the production of jams. The incorporation of mandacaru seeds and melon peels contributed to the functionality and attractiveness of the jellies and serves as an alternative for using waste.